A Morphometric Study of the Extraocular Muscles - Villarreal Silva, Eliud Enrique; Hinojosa Amaya, José Miguel; Bazaldúa Cruz, Juan José; Martínez Fernández, David. A.; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (Sociedad Chilena de Anatomía, 2013)
Extraocular muscles are important references in strabismus surgery and in placement of intraorbital devices. We analyzed extraocular muscles morphometry and possible anatomical variances of 20 orbits. We report the length, width, and points of insertion of the extraocular muscles. No anatomical variations in length, width and points of insertion were found. With regard to the rectus muscles, it was found that the superior rectus and lateral rectus are the longest muscles and that the width difference between the superior and inferior rectus is greater than that between the medial and lateral rectus and that the point of insertion of the rectus muscles has a variable morphology. The superior oblique muscle was smaller in caliber than the inferior oblique, as consistent with previous anatomical studies. Knowledge of the detailed morphology of extraocular muscles is fundamental in strabismus surgery and represents a key factor for the innovation of surgical techniques and orbital procedures.